Toxoplasma gondii Proteasome Subunit Alpha Type 1 with Chitosan: A Promising Alternative to Traditional Adjuvant - Zhengqing Yu; Wenxi Ding; Muhammad Tahir Aleem; Junzhi Su; Junlong Liu; Jianxun Luo; Ruofeng Yan; Lixin Xu; Xiaokai Song; Xiangrui Li (MDPI AG, 2021)
As an important zoonotic protozoan, Toxoplasma gondii (T. gondii) has spread around the world, leading to infections in one-third of the population. There is still no effective vaccine or medicine against T. gondii, and recombinant antigens entrapped within nanospheres have benefits over traditional vaccines. In the present study, we first expressed and purified T. gondii proteasome subunit alpha type 1 (TgPSA1), then encapsulated the recombinant TgPSA1 (rTgPSA1) in chitosan nanospheres (CS nanospheres, rTgPSA1/CS nanospheres) and incomplete Freund's adjuvant (IFA, rTgPSA1/IFA emulsion). Antigens entrapped in CS nanospheres reached an encapsulation efficiency of 67.39%, and rTgPSA1/CS nanospheres showed a more stable release profile compared to rTgPSA1/IFA emulsion in vitro. In vivo, Th1-biased cellular and humoral immune responses were induced in mice and chickens immunized with rTgPSA1/CS nanospheres and rTgPSA1/IFA emulsion, accompanied by promoted production of antibodies, IFN-γ, IL-4, and IL-17, and modulated production of IL-10. Immunization with rTgPSA1/CS nanospheres and rTgPSA1/IFA emulsion conferred significant protection, with prolonged survival time in mice and significantly decreased parasite burden in chickens. Furthermore, our results also indicate that rTgPSA1/CS nanospheres could be used as a substitute for rTgPSA1/IFA emulsion, with the optimal administration route being intramuscular in mass vaccination. Collectively, the results of this study indicate that rTgPSA1/CS nanospheres represent a promising vaccine to protect animals against acute toxoplasmosis.